Exploring the potential of extreme citizen science with Danish high school students using environmental DNA for marine monitoring - Leerhøi, Frederik; Rytter, Maria; Lillemark, Marie Rathcke; Randeris, Brian; Rix, Christian; Olesen, Jørgen; Olsen, Morten Tange; Møller, Peter Rask; Lundholm, Nina; Knudsen, Steen Wilhelm; Tøttrup, Anders P. (Frontiers in Marine Science, 2024)
Citizen science involves non-professionals assisting with scientific research, contributing data, and conducting experiments under professional guidance. In this paper, we describe the citizen science project DNA & life, based at the Natural History Museum of Denmark, which actively engages high school students in both fieldwork and advanced laboratory analyses by collecting and analyzing eDNA samples from marine environments across Denmark. The analysis is performed via speciesspecific real-time PCR and in a case study we present data gathered in the project from 2017-2023 with focus on the potential of eDNA detecting in use for species monitoring. The results include seasonal occurrence of Mnemiopsis leidyi and national distributions of selected species of particular ecological interest Perca fluviatilis, Anguilla anguilla, Neogobius melanostomus and Alexandrium ostenfeldii. In addition to the eDNA case study, we present a new way of conducting citizen science and eDNA analysis, as a development of the established DNA & life project. Local DNA laboratories are created to shorten the path from sampling site to laboratory facility, creating the possibility for Danish high schools to participate in a new version of the project. In close collaboration with the academic staff of the DNA & life project both teachers and students help develop facilities, protocols and laboratory analysis in an extreme citizen science and co-creation approach, where the participants are involved in a higher level of laboratory work and data analysis Allowing high school students to perform intricate molecular lab analyzes through an extreme citizen science approach has demonstrated encouraging outcomes and potential for data of high quality in terms of sampling and analyzing eDNA with the purpose of species monitoring and conservation.